2012
DOI: 10.4172/2155-9937.1000104
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Evaluation of Potential Disease Modification by Hylan G-F 20 (Synvisc®) Using dGEMRIC

Abstract: The objective of the present study was to utilize delayed Gadolinium Enhanced MRI of Cartilage (dGEMRIC), as a reflection of cartilage matrix integrity, to evaluate the effects of a specific hyaluronan, hylan G-F 20 (SYNVISC ® ; Genzyme Biosurgery, Cambridge, MA) in OA patients over the course of 6 months, and to utilize these data to determine effect size and power calculations for future studies. An open-label, single-blind exploratory study of patients having knee OA (Trail registration: NCT00949494) was pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…Such studies have already been performed and have shown a clinical improvement of HA injections compared to placebo [6,7]. Moreover, OA is generally a slow progressing disease in which no significant change in dGEMRIC outcomes was found at 14, 24 and 48 weeks follow-up compared to baseline in the control groups (n=15 and n=10 respectively) of two randomized controlled trials consisting of mild to moderate knee OA patients [25,26]. Thus, the absence of a control group was not considered a limitation to address our study aim, i.e.…”
Section: Methodsmentioning
confidence: 99%
“…Such studies have already been performed and have shown a clinical improvement of HA injections compared to placebo [6,7]. Moreover, OA is generally a slow progressing disease in which no significant change in dGEMRIC outcomes was found at 14, 24 and 48 weeks follow-up compared to baseline in the control groups (n=15 and n=10 respectively) of two randomized controlled trials consisting of mild to moderate knee OA patients [25,26]. Thus, the absence of a control group was not considered a limitation to address our study aim, i.e.…”
Section: Methodsmentioning
confidence: 99%